2023
DOI: 10.1039/d3cy01009k
|View full text |Cite|
|
Sign up to set email alerts
|

A two-dimensional MXene-supported CuRu catalyst for efficient electrochemical nitrate reduction to ammonia

Fang Zhao,
Guangxin Li,
Qianqian Hua
et al.

Abstract: As a carbon-free energy source and carrier, NH3 is an essential component utilized in agriculture, industry, and medicine. Currently, the main process for industrial ammonia is the Haber-Bosch process, which...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Therefore, under the traditional mode (Figure a), we evaluated the electrocatalysis performance of our membrane electrodes for the conversion of nitrate to ammonia (100 mL of 30 mg·L –1 NO 3 – -N, −1.3 V of voltage). Previous works have demonstrated that pristine Ti 3 C 2 T x is capable of converting the nitrate to ammonia, mainly induced by these Ti active centers. , As shown in Figure a, all these Cu-involved membrane electrodes display higher catalytic capacity compared to pristine Ti 3 C 2 T x , confirming that the presence of Cu nanoparticles is convenient for the conversion of nitrate, which agrees well with previous findings. , For example, the conversion rate of nitrate on TC 15 membranes reached 85% after reaction for 6 h while that on pristine ones was less than 25% under the same reaction time. Also, the catalytic performance of the TC x membrane electrodes increases with the loading amount of Cu under this electrode configuration (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, under the traditional mode (Figure a), we evaluated the electrocatalysis performance of our membrane electrodes for the conversion of nitrate to ammonia (100 mL of 30 mg·L –1 NO 3 – -N, −1.3 V of voltage). Previous works have demonstrated that pristine Ti 3 C 2 T x is capable of converting the nitrate to ammonia, mainly induced by these Ti active centers. , As shown in Figure a, all these Cu-involved membrane electrodes display higher catalytic capacity compared to pristine Ti 3 C 2 T x , confirming that the presence of Cu nanoparticles is convenient for the conversion of nitrate, which agrees well with previous findings. , For example, the conversion rate of nitrate on TC 15 membranes reached 85% after reaction for 6 h while that on pristine ones was less than 25% under the same reaction time. Also, the catalytic performance of the TC x membrane electrodes increases with the loading amount of Cu under this electrode configuration (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…MXenes can be implemented with other catalyst materials for improved NO 3 RR efficiency. Research has shown that the bimetallic synergistic effect may be used to increase the efficiency of NO 3 RR by simply dispersing Cu–Fe, 69 and Cu–Rh 70 on MXene.…”
Section: Design Strategies Of Electrocatalysts For No3rr To Nh3mentioning
confidence: 99%
“…Yang et al 26 investigated a multielement alloy nanoparticle catalyst with dispersed Ru (Ru-MEA) and other synergistic components (Cu, Pd, and Pt), which exhibited good stability and better catalytic performance than monometallic Ru. Zhao et al 27 synthesized Ru-Cu/Cu 2 O@Ti 3 C 2 catalysts, whose excellent nitrate catalytic performance originated from the synergistic interaction between multivalent Cu/Cu, abundant Ru metal active centers, and the excellent electrical conductivity of two-dimensional Ti 3 C 2 MXene. In addition, to reveal the synergistic mechanism of the catalytic performance of Cu on Ru, Chen et al 28 prepared a new catalyst with Cu-modified Ru nanoparticles (Cu-modified Ru/C NPs), which showed an NH 3 yield of 23.7 μmol h −1 cm −2 with an FE of 95%, which was superior to that of the Ru/C NPs (6.0 μmol h −1 cm −2 , FE of 66%).…”
Section: Alloys Of Tmesmentioning
confidence: 99%
“…Different electrocatalyst materials may lead to different reduction pathways and principles, and the performances of the electrochemical nitrate reduction reactions produced by different electrocatalyst designs are also very different. Recent studies on electrocatalysts have focused on noble metal-based catalysts (e.g., Rh, Ru, Pd, , and Au ), nonprecious metal-based catalysts (e.g., Cu, Fe, , Co, Ni, and Ti , ), and nonmetal-based catalysts (organic polymers, carbon-based, boron-based, and phosphorus-based). The electrochemical nitrate reduction reaction of noble metal-based materials such as palladium is characterized by high activity, good durability, and high cost, but its performance is far from ideal and is not conducive to practical wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%